Charity of Small- & Medium-Sized Businessesin a Russian Small Town: An Empirical Analysis - Marina Chernysheva (Journal of Economic Sociology, 2016)
The paper presents the results of an empirical study on the charity of smalland medium-sized businesses in a small Russian town. The aim of this article is to reveal motivations and barriers for small- and medium-sized businesses to participate in charitable activities. By the charity of a business, we mean a non-systematic provision of financial support to those in need. Different theoretical approaches are applied to explain the motivations for charitable activity in business. Critical theory implies that charity is used as an ideological tool aiming for a positive public image. Theories of solidarity conceptualize charity as a moral obligation to conform to the norms of the community. In the model of patrimonial domination, the authority distributes privileges in exchange for loyalty. This study was conducted in 2015–2016 in a small Russian town; 21 semi-structured interviews were carried out with the owners of small- and medium-sized businesses. In addition, 13 interviews were conducted with recipients of business donations and experts in the field of charity (including leaders of non-profit organizations, schools, local media, and government representatives). The empirical results show that business charity is a result of the relationships between businesses, the local community, and local authorities. The local community sets a stable social order of charity in a small town. However, the most stable and significant charitable donations from businesses are possible only in the system of patrimonial exchanges.